2018
DOI: 10.4103/ijpm.ijpm_223_17
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetics of BCR-ABL1 negative myeloproliferative neoplasms in India

Abstract: We report frequencies of JAK2 p. V617F, MPL exon 10 and CALR mutations in 130 patients similar to those reported in western literature. These mutations carry not only diagnostic but also prognostic relevance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
1
5
1
Order By: Relevance
“…JAK2 V617F mutation has a variable prevalence in the PV group ranging from 65% 13 to 97% 1 probably attributed to the sensitivity of the detection methods. In contrast to this study, an Indian report on 113 MPN patients revealed PV in 17.7%, ET in 30.1%, and PMF in 52.2% 14 . Furthermore, a study in Poland found that 29.8% (53/178) of patients were diagnosed with PV, 64% (114/178) with ET, and 6.2% (11/178) with PMF 15 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…JAK2 V617F mutation has a variable prevalence in the PV group ranging from 65% 13 to 97% 1 probably attributed to the sensitivity of the detection methods. In contrast to this study, an Indian report on 113 MPN patients revealed PV in 17.7%, ET in 30.1%, and PMF in 52.2% 14 . Furthermore, a study in Poland found that 29.8% (53/178) of patients were diagnosed with PV, 64% (114/178) with ET, and 6.2% (11/178) with PMF 15 .…”
Section: Discussioncontrasting
confidence: 99%
“…The JAK2 V617F mutation was present in 85.2% of all MPN patients. Rabadi N, et al, 14 reported this mutation in only 60% of all MPN patients. Many researchers have pointed to the impact of the JAK2 V617F allelic burden on the clinical and laboratory parameters of patients with MPN 4,[16][17][18] .…”
Section: Discussionmentioning
confidence: 98%
“…15.1% of total PMF & ET and 56.6% & 38.5% of JAK 2 V617F mutation negative PMF and ET cases, respectively 8. The present study also revealed similar frequencies of CALR mutation in ET, which isF I G U R E 4Microphotographs showing different intensity of staining in megakaryocytes.…”
supporting
confidence: 77%
“…When evaluated as a proportion of JAK2 V617F negative cases, the prevalence of CALR has been reported to be as high as 67% and 88% in cases of ET and PMF, respectively 1 . One of the earlier published Indian study, which included 59 PMF and 34 ET cases, has reported the frequency of CALR mutation as 23.7% and 15.1% of total PMF & ET and 56.6% & 38.5% of JAK 2 V617F mutation negative PMF and ET cases, respectively 8 . The present study also revealed similar frequencies of CALR mutation in ET, which is lower than the Western literature.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of our triple-negative mutations was 27.7%, which was similar to a Korean study (20%) [ 22 ]. Otherwise, the frequencies of the triple-negative mutations were found to be lower (10–15%) in Indian and Slovenia studies [ 11 , 28 ]. Other types of clonal mutations, such as ASLX1, EZH2, TET2, IDH1/IDH2, SRSF2 , and SF3B1 genes, may be demonstrated in PMF patients [ 29 ].…”
Section: Discussionmentioning
confidence: 99%